Osadki Karskogo morya (in russian, sediments of the Kara Sea). - Gorshkova, Tatyana I (PANGAEA, 1957)
The Kara scientific expedition of 1945, using the fishing trawler M. Gorkiy and survey vessel Osetr, took sediment samples in the Kara Sea in addition to other oceanographic work. The investigations of sediments composition was compared with biological and hydrological data obtained in the same areas. The sediments sampled were subjected to mechanical, mineralogical, chemical and faunistic analyses. During this survey iron-manganese concretions were recovered.
Annotated record of the Fe-Mn concretions recovered in the Kara sea during the M. Gorkiy survey in 1945
Keywords: Deposit type; DEPTH, sediment/rock; Description; Device of event; EG; Ekman grab; GORK45-10; GORK45-11; GORK45-14; GORK45-16; GORK45-17; GORK45-18; GORK45-19; GORK45-20; GORK45-21; GORK45-30; GORK45-32; GORK45-37; GORK45-39; GORK45-4; GORK45-7; GORK45-8; Gorkiy1945; Identification; Kara Sea; Maxim Gorkiy; NOAA and MMS Marine Minerals Geochemical Database; NOAA-MMS; Peterson grab; PETG; Position; Quantity of deposit; Sediment type; Visual description